IMPREGNATION OF 2-MERCAPTOBENZOTHIAZOLE ON DIATOMACEOUS EARTH AND ITS APPLICATION AS MERCURY(II) ADSORBEN IN AQUEOUS MEDIUM - Agung Purwanto; Narsito Narsito (Indonesian Journal of Chemistry, 2001)
An adsorbent was prepared by impregnating 2-mercaptobenzo-thiazole onto polystirene treated diatomaceous earth support. This adsorbent was then applied to adsorb mercury(II) in aqueous medium. The mercury(II) adsorption characteristics of the adsorbent was studied by the use of the original diatomaceous earth as reference. Interaction of mercury(II) and both of diatomaceous earth as well as MBT-diatomaceous were performed in a aqueous batch system to include the following parameters: (a) medium acidity and (b) mercury(II) adsorption characteristic on MBT-diatomaceous with and without the present of other metal ions. In the present work quantification of mercury(II) adsorption was done by determining the mercury concentration left in the solution after adsorption. A cold vapour-generation atomic absorption spectroscopy technic was used in this determination.The experiment results show, that the adsorption affinity of MBT-diatomaceous is higher than the original diatomaceous earth. The total adsorption energy of mercury(II) for diatomaceous earth (24.702 kJ/mol) and MBT-diatomaceous (46.942 kJ/mol) suggest that the interaction is chemisorption. The mercury(II) maximum adsorption on diatomaceous earth is obtained at pH 6, while similar adsorption on MBT-diatomaceous practically was not influenced by pH changes. The present of other metals, i.e. Fe(III), Co(II), Ni(II), Cu(II), Cd(II) and Zn(II) in solution does not give any appreciable influence to the adsorption affinity of MBT-diatomaceous to mercury(II); the total sum of the mercury(II) adsorbed is constantly high, almost 100 %.